Mediating and caring: line managers and employee commitment in the voluntary sector. (2nd January 2017) - Baines, Donna; Cunningham, Ian
ABSTRACT: Since the mid-1980s, New Public Management (NPM) and cuts in social funding have resulted in highly restructured organisations in the voluntary social services. These changes moved front-line supervisors, often referred to as line managers (LMs), away from direct, front-line service and replaced much of their supervision and support with tasks connected to contract compliance, particularly documenting progress on outcome metrics and other performance indicators. This article explores whether, in an era of NPM, LMs are able to apply leadership behaviours that encourage and sustain notions of altruism, care and commitment to the job among care workers in the voluntary social services sector. The article analyses qualitative interview data collected in five case studies in three countries (Australia, New Zealand and the UK) to explore the changing labour process in nonprofit services aimed at supporting society's most vulnerable people. The article contributes to understandings of changes in work process under austerity policies and adds to theorisations of work in the voluntary social services.